Plating of an isolated fracture of shaft of ulna under local anaesthesia and periosteal nerve block - Ahmad, Amir Adham (Trauma Case Rep, 2017)
Isolated fractures of shaft of ulna are common. Plate fixation with anatomic reduction is thought to produce the best functional results in closed or open fractures. Surgery can be done under general and various types of regional anaesthesia. We report a case of fracture shaft of ulna treated by plating under a combination of WALANT (wide awake, local anaesthesia, no tourniquet) using tumescent anaesthesia and periosteal nerve block as a day care procedure.